2021
DOI: 10.1128/jb.00027-21
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Ehrlichia chaffeensis Genes ECH_0660 and ECH_0665 Cause Transcriptional Changes in Response to Zinc or Iron Limitation

Abstract: Ehrlichia chaffeensis causes human monocytic ehrlichiosis by replicating within phagosomes of monocytes/macrophages. A function disruption mutation within the pathogen’s ECH_0660 gene encoding a phage head-to-tail connector protein resulted in the rapid clearance of the pathogen in vivo, while aiding to induce sufficient immunity in a host to protect against wild-type infection challenge. In this study, we describe the characterization of a cluster of seven genes spanning from ECH_0659 to ECH_0665, which conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The severity of infections seems to vary depending on the geographical area with more severe infections in the USA than in European countries ( Rar et al., 2021 ). Symptoms of HME are not specific and range from influenza-like symptoms to life-threatening disease ( Torres-Escobar et al., 2021 ). Chronic infections were observed for A. phagocytophilum in infected animals like horses, sheep, dogs, or lambs.…”
Section: Persistence and The Rickettsiales Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of infections seems to vary depending on the geographical area with more severe infections in the USA than in European countries ( Rar et al., 2021 ). Symptoms of HME are not specific and range from influenza-like symptoms to life-threatening disease ( Torres-Escobar et al., 2021 ). Chronic infections were observed for A. phagocytophilum in infected animals like horses, sheep, dogs, or lambs.…”
Section: Persistence and The Rickettsiales Ordermentioning
confidence: 99%
“…For example, the gene ECH_0660 was required for Ehrlichia growth in deer ( Cheng et al., 2013 ). Additional studies revealed ECH_0660-dependent upregulation of a cluster of seven genes during iron or zinc deprivation ( Torres-Escobar et al., 2021 ). A transposon mutagenesis library of E. chaffeensis by Wang and colleagues identified mutants for the genes ECH_0837 (coding for the metal ion binding protein MiaB) and ECH_1144 (coding for an outer membrane protein) with a significantly slower growth than wild-type E. chaffeensis in the macrophage cell line DH82 ( Wang et al., 2020 ).…”
Section: Persistence and The Rickettsiales Ordermentioning
confidence: 99%
“…chaffeensis phage head to tail connector protein ( phtcp ) gene (gene tag # ECH_0660) has minimal impact for its in vitro growth, while inducing attenuated growth in two different vertebrate hosts [ 12 , 13 ]. As the phtcp gene orthologs are broadly conserved in Anaplasma and Ehrlichia species [ 18 ], we reasoned that it serves as an ideal target for defining targeted mutagenesis in diverse Anaplasmataceae organisms. Indeed, the current study demonstrated such feasibility in A .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we reported that the phtcp gene disruption of E . chaffeensis causes an in vivo growth defect, possibly resulting from limiting the bacterial zinc and iron acquisition [ 18 ]. The data presented in the current study extends our prior data reporting that the functional phtcp protein is also critical for A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation